Perception of Youth about Coverage of Political Problems in Newspapers of District Karak, KP - Sarhadi, Nadir Saeed; Khan, Zahir Ullah; Ullah, Wali (Annals of Human and Social Sciences, 2023)
The current study identifies the perception of youth about coverage of political problems in newspapers of district Karak, KPK in light of agenda setting and framing theories. The four leading Urdu dailies: The Karak Time, Awami Dastak, Sada-e-Lawaghar and Janisar-e-Pakistan were selected. The data were collected through written questionnaire, using simple random sampling technique in both genders and students of different educational background, aged between 18-30 years at Khushal Khan Khattak University, Karak (KKKU.K) and other affiliated collages, (Government post graduate College Karak (GPGC) and Government Degree College/ GDC), analyzed by using SPSS. The results indicate that these four leading papers covered the political problems on the agenda of politicians to propagate their political ideologies to the common masses to gain their political gain and given more salience to maximize their profit. Youth in District Karak, KPK have a negative perception about coverage of political problems in newspapers.